Proposta de critérios para dimensionamento de pessoal docente em uma Instituição Federal de Ensino Superior - Guimarães, Pedro Santos (2023)
Staff planning is essential to the success of an organization’s operations. In the case of the Federal Higher Education Institutions (IFES), it is even more relevant, given the limited flexibility in people management policies and legal and budgetary restrictions. This study aims to propose a model for staff sizing and allocating teaching positions in a Brazilian Federal University. In order to identify relevant criteria and variables, a literature review was conducted, with a search for existing norms in the IFES, as well as a detailed study of the history and current situation of the Federal University of Uberlândia (UFU), the target institution of the research. The problem was formulated using a linear programming model, with different teacher profiles as the decision variables. Each profile has a capacity for weekly classes and tutoring, as well as time available for activities beyond teaching – extension, management and research. The model’s constraints include, among others, in the number of classes that must be offered per week, number of students to be tutored, minimum and maximum values of the average workload of classes per teacher and maximum acceptable percentages for each profile. Different performance measures can be used as objective functions, such as minimizing the total number of teachers allocated or maximizing the available time for activities beyond classes. The Analytic Hierarchy Process (AHP) was used to establish priorities and weights for each criterion, combining them into a single objective function. The importance of each criterion is defined by the institution’s people management policy and can be adjusted as necessary. The results showed that the proposed model can be useful as a decision support tool, and the presented solution must be evaluated to suit the context and reality of the university. The model is flexible and can be adjusted or expanded to meet new constraints, making it suitable for use by other Federal Higher Education Institutions (IFES). As the technological product of the research, a software implementation of the model was developed and made available for use and improvement.